If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5h + -12 = 4h + 7 Reorder the terms: -12 + 5h = 4h + 7 Reorder the terms: -12 + 5h = 7 + 4h Solving -12 + 5h = 7 + 4h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-4h' to each side of the equation. -12 + 5h + -4h = 7 + 4h + -4h Combine like terms: 5h + -4h = 1h -12 + 1h = 7 + 4h + -4h Combine like terms: 4h + -4h = 0 -12 + 1h = 7 + 0 -12 + 1h = 7 Add '12' to each side of the equation. -12 + 12 + 1h = 7 + 12 Combine like terms: -12 + 12 = 0 0 + 1h = 7 + 12 1h = 7 + 12 Combine like terms: 7 + 12 = 19 1h = 19 Divide each side by '1'. h = 19 Simplifying h = 19
| -8x+29=-7x | | 3=11+a | | .7(3x-5)+3.9x=14.5 | | 1-10x=91 | | 6x-12=8x-9 | | 2x-1=+11 | | -46-14n=-8(-6b+1) | | 3d+3c+5c= | | (7a+3)+(-a-5)=14 | | 9x^2-6x+6=0 | | -7(x+1)+(14x)=7(x+3)-14 | | 2/3(x+5)=4/9 | | 2m^2+10m=-12 | | 130-7x=38x+20 | | 32w^3-2v^4w^3=0 | | x^3-2x^2-9x-2=0 | | 27.5=2.5q+1q-4 | | 4(x+2)-2(x-4)=32 | | y+3=24 | | n+35=46 | | X^3-27=y | | 6-8x=8x+22 | | 3-0.5x=-2 | | 2x+15=44+8x | | 6-2(3x-1)+2=2 | | 3x^4-81x=0 | | -n-5=-21 | | 7h+5=138 | | -6-y=-12 | | 15x^2-5x-4+64=180 | | z^2+18z+70=0 | | 3x-14=16x-34 |